Effectiveness of metronidazole as an adjunct to scaling and root planing in the treatment of chronic periodontitis: a systematic review and meta‐analysis. (14th May 2013) - Sgolastra, F.; Severino, M.; Petrucci, A.; Gatto, R.; Monaco, A.
<x xml:space="preserve">Abstract</x> Background Metronidazole (MET) has been suggested as an adjunct to scaling and root planing (SRP) in the treatment of chronic periodontitis. However, its clinical effectiveness and effects on periodontal pathogens remain to be defined. The present meta‐analysis assessed the scientific evidence concerning the effect of MET adjunctive to SRP as compared to SRP alone. Methods A literature search of electronic databases was performed for articles published through December 16, 2012, followed by a manual search of several dental journals. A meta‐analysis was conducted according to recommendations of the Cochrane Collaboration and PRISMA. Weighted mean differences (MDs) and 95% confidence intervals (CIs) were calculated for probing depth reduction, clinical attachment level gain, bleeding on probing index and suppuration. All outcomes were evaluated as changes from baseline to the end of follow‐up. Heterogeneity was assessed with the chi‐squared‐based Cochran Q test and I2 statistic. The level of significance was set at p < 0.05. Results After the study selection process, six randomized clinical trials were included in the meta‐analysis. The results of the meta‐analysis indicated that SRP + MET provided additional benefits when compared to SRP alone in terms of probing depth reduction (MD, 0.18; 95% CI, 0.09–0.28; p < 0.05) and clinical attachment level gain (MD, 0.10; 95% CI, 0.08–0.12; p < 0.05). No evidence of heterogeneity was detected. Conclusion The meta‐analysis results seem to support the effectiveness of adjunctive MET with SRP compared to SRP alone. However, given the low number of included studies and limitations of meta‐analysis, future studies are needed to confirm these results.